Dispensability of nanos mRNA localization for abdominal patterning but not for germ cell development. - Gavis, E.R.; Chatterjee, S.; Ford, N.R.; Wolff, L.J. (Mechanisms of Development, 2008)
The development of a functional germline is essential for species propagation. The nanos (nos) gene plays an evolutionarily conserved role in germline development and is also essential for abdominal patterning in Drosophila. A small fraction of nos mRNA is localized to the germ plasm at the posterior pole of the Drosophila embryo, where it becomes incorporated into the germ cells. Germ plasm associated nos mRNA is translated to produce a gradient of Nos protein that patterns the abdomen, whereas the remaining unlocalized RNA is translationally repressed to allow anterior development. Using transgenes that compromise nos mRNA localization and translational regulation, we show that wild-type body patterning can ensue without nos mRNA localization provided that nos translation is properly modulated. In contrast, localization of nos to the germ plasm, but not translational regulation, is essential for nos function in the developing germ cells. We propose that an imperative for nos localization in producing a functional germline has preserved an inefficient localization mechanism.